The anterior scleral thickness in primary open-angle glaucoma with high myopia - Li, Mu; Chen, Liwen; Luo, Zhaoxia; Yan, Xiaoqin (Frontiers in Medicine, 2024)
Purpose: To investigate and compare the anterior scleral thickness (AST) among high myopia (HM), primary open-angle glaucoma (POAG), and POAG with HM (HMPOAG) groups. Methods: Thirty-two HM eyes, 30 POAG eyes, and 31 HMPOAG eyes were included. The Schlemm’s canal (SC) area, trabecular meshwork (TM) thickness, scleral spur (SS) length and AST were measured with swept-source optical coherence tomography. AST was measured at 0mm (AST0), 1mm (AST1), 2mm (AST2), and 3mm (AST3) from SS. Results: AST was significantly thinner, SS length was significantly shorter, and TM thickness was significantly thinner in HMPOAG group than in HM and POAG groups (all p<0.05). In addition, SC area of HMPOAG group was also significantly smaller than that of HM group (p<0.001). Conclusions: HMPOAG group had thinnest AST, shortest SS, thinnest TM and smallest SC. The thinnest AST might contribute to the shortest SS, and further to the thinnest TM and smallest SC in HMPOAG group. AST might be a novel clinical indicator in the prediction and evaluation of POAG.